Consumption of Lactobacillus casei fermented milk prevents Salmonella Reactive Arthritis by modulating IL-23/IL-17 expression - Noto Llana, Mariangeles (2013)
Reactive arthritis is the development of sterile joint inflammation as a sequel to a remote infection, often in the gut. We have previously shown that a low dose of S. enteritidis inoculated to streptomycin-pretreated mice generates a self-limiting enterocolitis suitable for studying reactive arthritis. Here we show that consumption of Lactobacillus casei prior to infection abolishes intestinal and joint inflammation triggered by Salmonella. BALB/c mice were sacrificed after infection; intestinal and joint samples were analyzed for histological changes and expression of cytokines. TNF- α was measured by ELISA and the expression of IL-1β, IL-6, IL-10, IL-17, IL-23 and TGF-β was assessed by qPCR. L. casei consumption prevented Salmonella-induced synovitis, the increment of TNF-α in knees and the increase of IL-17 expression in popliteal and inguinal lymph nodes. At intestinal level consumption of L. casei drastically diminished S. enteritidis invasiveness and shortened splenic persistence of the pathogen. Bacterial loads recovered at days 2 and 5 from Peyer?s patches were 10-fold lower in mice fed with L. casei. In accordance, we found that the augment in gut permeability induced during enterocolitis was decreased in those animals. Consumption of L. casei prior to infection failed to increase anti- inflammatory molecules such as IL-10 and TGF-β in the intestine. On the other hand, consumption of L. casei abrogated the expression of TNF-α, IL-17, IL-23, IL-1β and IL-6 in cecum and mesenteric lymph nodes. These cytokines are needed for differentiation of immune cells involved in the development of reactive arthritis such as Th17 and γδ T cells. Trafficking of these inflammatory cells from the gut to the joints has been proposed as a mechanism of generation of reactive arthritis. Our results suggest that L. casei consumption prevents Salmonella-induced synovitis by altering the intestinal milieu necessary for differentiation of cells involved in the generation of joint inflammation.